2020
DOI: 10.3934/dcdsb.2019200
|View full text |Cite
|
Sign up to set email alerts
|

Poxvirus, red and grey squirrel dynamics: Is the recovery of a common predator affecting system equilibria? Insights from a predator-prey ecoepidemic model

Abstract: In Europe, the Eastern grey squirrel is an allochthonous species causing severe impacts on the native red squirrel. The invasive species establishes complex relationships with the native one, out-competing it through resource and disease-mediated competition. However, recent research shed light on the potential role of a predator, the pine marten, in reversing the outcome of the competition between squirrels. Here, we investigate this hypothesis developing a one predator-two prey ecoepidemic model, including d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 27 publications
(31 reference statements)
0
6
0
Order By: Relevance
“…That model had no density-dependent regulation of the infected populations, and the thresholds for transition between infected steady states were presented in terms of the host population densities rather than the reproduction numbers that we employ. The study presented in [17] addressed two squirrel species, SQPV and the pine marten as predator, but did not explicitly model infection dynamics in the grey squirrel. One feature of our model that differs from most previous models is the inclusion of the infected but not infectious state A g .…”
Section: On Eco-epidemiological Dynamics Involving Three Trophic Levelsmentioning
confidence: 99%
See 2 more Smart Citations
“…That model had no density-dependent regulation of the infected populations, and the thresholds for transition between infected steady states were presented in terms of the host population densities rather than the reproduction numbers that we employ. The study presented in [17] addressed two squirrel species, SQPV and the pine marten as predator, but did not explicitly model infection dynamics in the grey squirrel. One feature of our model that differs from most previous models is the inclusion of the infected but not infectious state A g .…”
Section: On Eco-epidemiological Dynamics Involving Three Trophic Levelsmentioning
confidence: 99%
“…It is possible that the predator has effects on grey and red squirrels that add to the direct effect of increased mortality. In the presence of an active predator, the squirrel species may experience stress in a landscape of fear to different degrees that may influence their competitive ability [17,[43][44][45][46]. The figure shows the regions in the (K r , K g ) plane where each steady state is stable.…”
Section: Infected Steady Statesmentioning
confidence: 99%
See 1 more Smart Citation
“…The study also found a negative correlation between grey squirrels and pine marten (Martes martes), a native mustelid whose numbers are increasing, and a positive correlation between pine marten and red squirrels. Theoretical studies using a two prey-one predator ecoepidemic model have also shown that the predator (pine marten) can destabilise the previous grey squirrel dominant equilibria, favouring the native red squirrel (Travaglia et al 2020). Thus, the impact of a native predator could aid red squirrel survival in the United Kingdom and Ireland via a reduction in grey squirrel density and geographic spread (Twining et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The replacement between the two species is mainly due to exploitation competition for food resources, with the American species being more efficient in their use [34]. In Great Britain, however, grey squirrels carry a squirrelpox virus which is lethal for the red squirrel and this diseases-mediated competition increases the speed of the replacement [30,31,25] Models to explore two species interaction have been recently investigated, [31,2,21]. Alien species could also act as amplifiers of local pathogens.…”
mentioning
confidence: 99%